A facile synthesis of two ionized fluorescent carbon dots and selective detection toward Fe2+ and Cu2+. Issue 7 (4th June 2020) - Gao, Li; Wu, Datong; Tan, Wensheng; Pan, Fei; Xu, Jiale; Tao, Yongxin; Kong, Yong
Abstract : Two ionized carbon dots were prepared with different optical properties and applied for the selective detection of Fe 2+ and Cu 2+ . Abstract : In this study, a facile synthesis of two ionized carbon dots (CDs-2 and CDs-3) is reported, in which different ionic pairs are formed at the surface of the carbon core. In contrast to CDs-3, the accumulation of carbon core can be clearly observed in the TEM image of CDs-2. This is due to the linkage of the dibromine alkyl group. Compared with naked CDs in the absence of the ionic pair, the maximum emission wavelength undergoes a red-shift of nearly 60 nm. Moreover, protic solvents (water, ethanol and N, N ′-dimethyl formamide) have an apparent effect on the emission intensities of CDs-2 and CDs-3. The time-resolved average lifetimes of CDs-2 and CDs-3 are calculated as 56.34 ns and 54.50 ns, respectively. Furthermore, they both have much better fluorescence stability in the solution with pH ranging from 2 to 11 due to the presence of the imidazolium cation. It is interesting to see that CDs-2 and CDs-3 have much different responses towards Cu 2+ and Fe 2+ . The CDs-3 solution generates clear fluorescence quenching when treated with Fe 2+ . In brief, we believe that these findings can inspire more research developments in the synthesis and further application of functional CDs.